Parameters of radical resection in laparoscopic and open colon and rectal cancer surgery - Krdžić, Igor; Kenić, Marko; Šćepanović, Milena; Soldatović, Ivan; Ilić Živojinović, Jelena; Radovanović, Dragan (Vojnosanitetski pregled, 2021)
Background/Aim. In colon and rectal cancer surgery, resection is considered radical when circumferential, proximal and distal resection margins are without the presence of tumor cells. Concept of total mesorectal excision in rectal surgery involves complete removal of the tumor with mesorectal fascia which surrounds lymph nodes, lymphatics and blood vessels. The aim of this study was to determine whether laparoscopic approach provides all parameters of oncological radicality as open surgery of colorectal cancer. Methods. The study included 122 patients with carcinoma of colon and rectum, divided into two equal groups: patients operated on by laparoscopic and those operated on by open approach. In colon surgery we analyzed proximal and distal resection margins, and the number of removed lymph nodes, and in rectal surgery: proximal, distal and circumferential resection margins, and the number of removed lymph nodes. Results. Both groups were comparable in age, sex, American Society of Anesthesiologists (ASA) score, tumor localization, tumor size, and type of surgical operation performed. According to localization of the tumor, the most commonly performed operation was anterior resection of the rectum (60.7% vs. 59%). There was no case of the tumor involvement of the distal margin. Average proximal distance from the tumor on the fixed specimen was 100 vs. 120 mm with statistical significance (p < 0.001). Distal margins were not significantly different, 40 mm in both groups (p = 0.143). In two cases we had circumferential resection margin (CRM) of 1 mm (7.7%) in the laparoscopic group, and in three cases operated conventionally CRM was 1 mm (8.8%). The average number of removed lymph nodes was 15 vs. 16, respectively. Length of hospital stay for patients assigned to the laparoscopic surgery was significantly shorter than for patients operated on by the open approach. Concerning postoperative complications, no significant difference was found between groups. The overall postoperative morbidity was 18% vs. 21.3%, respectively. Conclusion. With laparoscopic approach it is possible to provide all parameters of oncological radicality similarly to the open surgery of colorectal cancer.